Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Show That :

$$\sum_{n=1}^{\infty} \frac{1}{n 2^{2n+1}} = \ln \left(\frac{2}{\sqrt{3}}\right)$$

I could show convergence. (I dont need to show that this converges). However I couldn't figure how to show the value.

share|improve this question
Did you try $\sum_{n=1}^{\infty} \frac{y^n}{n} = -\ln \left(1-y\right)$ –  Kirthi Raman May 23 '12 at 12:53
"I dont need to show that this converges" implies it is a homework in my opinion. –  Wok May 23 '12 at 12:57
@wok adding the homework tag to something that is not obviously homework is considered impolite. This could be a question from a textbook. –  Chris Taylor May 23 '12 at 12:59
I'm going to delete the homework tag. Ehrlick, if it is homework, please add the homework tag back in. –  Gerry Myerson May 23 '12 at 13:01
@The-Ever-Kid, we don't add the homework tag to other people's questions unless the person asking the question says that it's homework. We encourage the poster to add the tag, if it is homework. –  Gerry Myerson May 24 '12 at 13:49

3 Answers 3

$$ \begin{align*} \sum_{n=1}^{\infty} \frac{y^n}{n} &= -\ln \left(1-y\right) \hspace{15pt} {\textit{apply }} \hspace{5pt} y=\frac{1}{x^2}\\ \sum_{n=1}^{\infty} \frac{1}{n x^{2n}} &= -\ln \left(1-\frac{1}{x^2}\right) \\ \sum_{n=1}^{\infty} \frac{1}{n 2^{2n+1}} &= \frac{1}{2}\sum_{n=1}^{\infty} \frac{1}{n 2^{2n}} = -\frac{1}{2}\ln \left(1-\frac{1}{4}\right)\\ \end{align*} $$

Do the rest to simplify and get what you want.

share|improve this answer
$$ f(x) = \sum_{n=1}^{\infty} \frac{x^n}{n} \Rightarrow f'(x) = \sum_{n=1}^{\infty} x^{n-1} = \frac{1}{1-x} $$ $$ f(x) = \int \frac{1}{1-x} \ dx = -\ln(1-x) + c $$ $$ but : f(0) = 0 \Rightarrow 0 + c = 0 \Rightarrow c = 0 \Rightarrow f(x) = \sum_{n=1}^{\infty} \frac{x^n}{n} = -\ln(1-x) $$ –  what'sup Aug 13 '13 at 15:21
@what'sup An alternative derivation: Start with$$\lim_{\epsilon\to0}\dfrac{(1-x)^\epsilon-1}\epsilon$$which L'Hôpital shows is equal to $\ln(1-x)$. Then, use Newton's generalized binomial theorem to expand that into a series. –  columbus8myhw Oct 12 '14 at 17:23

There are various options - here is one: I won't work it through to the end.

Write $$f(t)=\sum_{n=1}^{\infty} \frac{t^n}{n 2^{2n+1}}$$

Then $$f'(t)=\sum_{n=1}^{\infty} \frac{t^{n-1}}{2^{2n+1}} = \frac 1 8 \sum_{n=1}^{\infty} \left(\frac t 4\right)^{n-1}$$

Which is a geometric series ...

share|improve this answer
Good answer! You have to be a little bit careful about the domain of definition of $f$ (because the radius of convergence of $f$ is 4, by the ratio test) but as we are only interested in $t=1$ this is of course no problem. –  Nils Matthes May 23 '12 at 13:13

Artin's comment pretty much answers the question.

Did you try $\sum_{n=1}^\infty\frac{y^n}{n}=-ln(1-y)$

Just observe that your series actually is $$\frac{1}{2}\sum_{n=1}^\infty\frac{\left(1/4\right)^n}{n}$$ As this is homework, you should also, I guess, be careful to check radius of convergence...

share|improve this answer
$$ f(x) = \sum_{n=1}^{\infty} \frac{x^n}{n} \Rightarrow f'(x) = \sum_{n=1}^{\infty} x^{n-1} = \frac{1}{1-x} $$ $$ f(x) = \int \frac{1}{1-x} \ dx = -\ln(1-x) + c $$ $$ but : f(0) = 0 \Rightarrow 0 + c = 0 \Rightarrow c = 0 \Rightarrow f(x) = \sum_{n=1}^{\infty} \frac{x^n}{n} = -\ln(1-x) $$ –  what'sup Aug 13 '13 at 15:21

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.